(untitled) (Research, Society and Development, 2022)
The fruit of Myrciaria dubia is rich in bioactives, these have a high content of ascorbic acid and phenolic compounds, for this reason, the fruit has been gaining prominence for its antioxidant capacity. The aim of this study was to evaluate whether different extracts obtained from M. dubia fruit peels influence the antioxidant activity. 70% hydroalcoholic (EHA) and 10 and 20% glycolic extracts (EG10 and EG20) were obtained from bark from a moderately coarse powder with loss on desiccation of 13.53%, total ash of 1.95%, ash insoluble in acids of 0.057%, pH 2.53±0.05 and swelling index of 1.1ml. The extracts were characterized as to the content of ascorbic acid and total polyphenols and the antioxidant activity determined by DPPH and ABTS+. The EHA showed 7011±39 mg/100ml of ascorbic acid and 7.75% of total polyphenols, while in the EG10 and EG20 the ascorbic acid content was 3034±0 and 6137±0 mg/100mL and total polyphenols of 2 .65 and 3.55% respectively. The extracts showed DPPH antioxidant capacity with IC50 of 11.80, 48.95 and 25.26 µg/mL and ABTS+ of 92.91±0.205, 74.59±0.259 and 77.21±1.34% in the EHA extracts, EG10 and EG20, respectively. The extracts have important contents of bioactive compounds, however, the solvent influenced the content and biological activity, with EHA having the highest content of bioactives, which also reflected in its greater antioxidant capacity.